The Cauchy problem for Choquard equation with an inverse‐square potential. (27th October 2021) - Liu, Jinxing; Wang, Xiongrui; Zhou, Jun; Deng, Xiumei
Abstract : This paper deals with the Cauchy problem for Choquard equation with an inverse‐square potential, and the infinite conditions for solutions existing globally and blowing up in finite time are given, which generalize the recent results about this model.